Tocqueville : the Ancien Régime and the French Revolution - Tocqueville, Alexis de, 1805-1859 (Cambridge texts in the history of political thought., 2011)
"This new translation of an undisputed classic aims to be both accurate and readable. Tocqueville's subtlety of style and profundity of thought offer a challenge to readers as well as to translators. As both a Tocqueville scholar and an award-winning translator, Arthur Goldhammer is uniquely qualified for the task. In his Introduction, Jon Elster draws on his recent work to lay out the structure of Tocqueville's argument. Readers will appreciate The Ancien Régime and the French Revolution for its sense of irony as well as tragedy, for its deep insights into political psychology, and for its impassioned defense of liberty"--